CODESRIA Bulletin Online, No. 11, July 2022 - European War and Global South Perspectives - Ndlovu-Gatsheni, Sabelo J. (CODESRIA Bulletin, 2022)
"If the greatest trick the devil pulled was convincing the world he does not exist, then the proudest achievement of Western imperialism is the delusion that we have moved beyond racism, that we are in a post-racist society." (Kehinde Andrews 2021:xxvii) "Therefore, it is submitted that African nations will absorb international shocks based on their relationships with specific circumstances." (Toyin Falola 2022:18) Introduction The global South perspectives on the Russia–Ukraine War reflect the multiplexity of the power dynamics, complex state affiliations and important transactional engagements of states within today’s internationalism. Simplistic attempts to divide the contemporary world into autocracies on the one side and democracies on the other are not helpful in the current global circumstances. The dichotomous Cold War ideological thinking is no longer adequate for understanding the current hetararchies of power, multiplexities of affiliations and complex transactional relations of states. The global South perspectives and responses to the Russia–Ukraine War are not only complex but are informed by equally complex histories, memories, current realities as well as strategic, tactical and transactional calculations that determine alliance formations and voting patterns at the United Nations General Assembly. A regional sampling, which considers the complexities, multiplexities and divisions among the constitutive members of the regions of the global South, is examined here as it affords a mapping of common patterns of response and perspective from Africa, the Middle East, Asia and Latin America. It also offers a reading of issues at stake in the global South’s interpretation of contemporary internationalism. What is emerging is that states across the regions of the global South ‘are hedging their belts between Russia and the US-led Western camp, playing on time to better evaluate the impacts of the war and ease the restraints it is imposing on the fragile economies and social fabrics of the region’ (Hamzawy et al. 2022:1). This is expected from a world that is still trying to emerge from the Covid-19 pandemic. The Russia–Ukraine War at the Present Conjuncture If the Euro-North-American-centric neoliberal international order failed its test in the Middle East, its burial will be in Eurasia. The Russia–Ukraine War, which broke out on 24 February 2022, is a signal of the violent end of the Euro-North-American-centric neoliberal international order. This should not be mistaken for an end of the capitalist world system. What is imbricated in this war is the forces of rewesternisation on the one hand and of dewesternisation on the other hand (the stormtroopers of which are the E7 — the emerging seven, constituting China, India, Brazil, Mexico, Russia, Indonesia and Turkey), which are forcing global history to take a corner (Mahbubani 2018:7). At the centre of rewesternisation and dewesternisation is a struggle over the control of the colonial matrix of power and the possibilities of a shift of capital from the Atlantic circuit to a Sinocentric circuit. Kishore Mahbubani (2018:3) captured this reality in these words: ‘In the early twenty-first century, history turned a corner, perhaps the most significant corner humanity has ever turned — yet the West refuses to accept or adapt to this new historical era.’ The refusal of the West to adapt to a world it can no longer dominate is signified by such initiatives as the new law that the United States 117th Congress 2nd Session deliberated on 28 April 2022, which seeks to counter what they termed ‘the malign influence and activities of the Russian Federation and its proxies in Africa’ (Countering Malign Russian Activities in Africa Act, 28 April 2022). In this thinking, the US behaves as though the whole world is its province, and that Russia–Africa relations have to be assessed and controlled from Washington. What is even more worrying is the open expression of the US’s strategy to manipulate African governments and their people into dissociating from Russia, including using what is called ‘aid assistance’ (see Countering Malign Russian Activities in Africa Act, 28 April 2022). All these are signs that rewesternisation is in trouble and that the Russia–Ukraine War is being used to advance it. Unlike other wars, such as the Gulf War before it and the ongoing war in Syria, the Russia–Ukraine War has attracted widespread media coverage and numerous opinion pieces, perhaps because it is taking place in Europe, which has been self-representing as a zone of peace and bastion of rational disputation. What is beyond dispute is that every shift in global order since the dawn of Euromodernity has been accompanied by conflicts, violence and wars. Even when the modern world rebooted itself, shifting from empires to modern nation-states, conflicts, violence and wars became its signature. The Cold War coloniality, from 1945 to 1989, was never cold outside Europe and North America. It was characterised by what became known as ‘proxy wars’. With regard to the Cold War, Mahmood Mamdani (2004:254) posited that small states were faced with the reality of seeking protection from ‘one or another international bully’, yet others who were imbued with the Bandung spirit ‘tried to pioneer an alternative international order, one dedicated to two goals: to hold every bully accountable to minimal norms and guarantee a share of justice to every historical victim’. The outbreak of the Russia–Ukraine War in February 2022 has presented the smaller states (a majority in the global South) with a new situation where such decisions have to be made again, albeit under different international circumstances characterised by multiplexities of affiliations and hetararchies of power criss-crossing the invented divide of autocracies and democracies. Even what became known as the post-Cold War dispensation, celebrated as the age of triumphalism of liberal democracy, human rights and the rule of markets, witnessed the outbreak of what the United States leadership labelled the ‘Global War on Terror’ (GWT). The 9/11 incident became its immediate cause. The noble United Nations notion of the ‘Right-to-Protect’ (R2P) was skyjacked by the US and imbricated in its imperial ‘preventive wars’ strategy. In the process, blood continued to flow from conflicts and wars that were justified as protecting the people, such as those in Iraq and Libya. What must be underscored is that whenever the modern world system finds itself besieged by revolutionary antisystemic forces, it responds either by violently crushing them or by accommodating them into the very system these forces seek to destroy. Accommodating revolutionary antisystemic forces has always involved the rise of a new global order, which functions to give the system a new lease of life. This happened after 1945, when the modern world system was besieged by anticolonial forces (some revolutionary and others reformist). A new global order emerged, which used the United Nations (UN) to invite every newly born nation-state into the system they had sought to destroy. Consequently, the so-called ‘postcolonial’ states in Latin America, Caribbean, Asia and Africa occupied the lowest echelons of the modern world system, without any veto power. What is becoming obvious is that a shift from one global order to another is a strategy to preserve the modern world system rather than change the system itself. For example, what Carl Schmitt termed the ‘second nomos’ of the earth, which emerged in the fifteenth century with the rise of Europe and North America, has survived the decolonisation of the twentieth century. The physical empire mutated into the cognitive empire. Direct colonialism morphed into neocolonialism. Ex-colonies became spheres of influence. Ex-empires could not let go. Robert Gildea (2019) introduced the concept of ‘empires of the mind’ and explained how they constructed a ‘global financial republic’ which used debt as a control mechanism. Currently, the neoliberal international order has fallen into its deepest crisis. It is besieged by systemic, ecological, epistemic and ideological crises. The combination of the global financial crisis, the Covid-19 pandemic, the rise of right-wing politics, and the outbreak of the Russia–Ukraine War are signatures of an interregnum. The United States of America (USA) and its European partners in the European Union (EU) are busy trying to patch up the Euro-North-American-centric modern world system through what Walter Mignolo (2021) termed ‘rewesternisation’. Invocations of notions of ‘the free world’ of democracies on the one hand, and autocracies on the other hand, are part of propping up the neoliberal international order. Russia is identified as a spoiler together with China. They are the face of what is known as ‘dewesternisation’ and the possibilities of multipolarity (Mignolo 2021). The Russia–Ukraine War is at the centre of the contending forces of ‘rewesternisation’ and ‘dewesternisation’. Because the modern world has undergone increased global human entanglements and the ever-evolving global capitalist economic system has used capital to link every economy to it, the Russia–Ukraine War is impacting every country. The Russian Federation is a great power with widespread connections to the rest of the world, and its military invasion of a small power like the Ukraine ignites fear among smaller states of a return of empire. This fear is even more meaningful for the Eastern European republics, most of which emerged from the collapse of the Union of Soviet Socialist Republics (USSR). The Soviet Union was an empire that used Cold War coloniality to spread and maintain control over Eastern Europe and beyond. Read from this perspective, Eastern European decolonisation can be best named ‘de-Cold War’, to borrow a concept from Kuan-Hsing Chen (2010). The Russian military invasion of Ukraine has set in motion numerous debates about the state of multilateralism, rule-based neoliberal internationalism, the fate of self-determination and the territorial integrity of small states, and even the future of the United States leadership of the modern world. How appropriate is it to name it the Russia–Ukraine War? Is this is not another complex imperialist war, taking place at a time when the neoliberal international order is in crisis? Imperialist wars always turn out to be world wars even if they start as inter-state wars caused by a collapse in bilateral relations. Behind what appears to be a conflict between Russia and Ukraine, there is the deep involvement of the European Union (EU) and the United States of America (USA). Already it has happened that those people who have been designated and classified as Black have been caught in between, betwixt and indeed in the middle of the war. This emerged poignantly during the evacuation of refugees. Train stations in Ukraine and on the borders of Eastern Europe became sites of racism as Africans in particular were barred from boarding trains and crossing borders to safety. This racist phenomenon emerged within a context not only of war but also of animated debates on the subjects of ‘antiblackness’ and global Black Lives Matter movements. At another level, the refugee crisis provoked by the war revealed how Ukrainians running away from the war zone were openly welcomed in Europe, compared to Syrians and others escaping war zones outside Europe. The hypocrisy of those states that claim to be democracies and paragons of human rights protections has been laid bare in their differential treatment of refugees. What has also added to the complexity of the war are claims of the Russian invasion amounting to a Holocaust by President Volodymyr Zelenskyy of Ukraine and the justification of the invasion by President Vladimir Putin of Russia as an operation aimed at de-Nazification. My interest in this piece is global South perspectives of the war. Reading the Russia–Ukraine War from the Global South In The Darker Nations: A People’s History of the Third World (2007), Vijay Prashad not only explained that the global South is not a place but a project and meticulously documented how the global South has been at the forefront of the anti-imperialist struggle, going as far back as the Haitian Revolution. It was also the global South that was consistently critical of the post-1945 international order. What the global South put on the global table were three major issues: ‘political independence, non-violent international relations, and the cultivation of the United Nations as the principle for planetary justice’ (Prashad 2007:11). It was the global South that introduced what Prashad (2007:12) termed ‘internationalist nationalism’, expressed by the Bandung spirit and tricontinentalism. The ‘against war’ positionality of the global South came from the experience of a people who had walked under the shadows of death many times, beginning with their enslavement, subjection to genocides, and subjection to colonialism right up to neocolonialism and underdevelopment. Therefore, reading the war from the global South makes a strong case to revisit not only the question of how internationalism itself is constituted by coloniality but also the futility of the paradigm of war as a solution to modern problems. In his The New Age of Empire: How Racism and Colonialism Still Rule the World (2021), Kehinde Andrews delved into the depth of the violence of Euromodernity as he demolished the ‘self-congratulatory myth’ that the rise of the West was due to three great endogenous revolutions: science (the Renaissance and Enlightenment), industry (the Industrial Revolution), and politics (the French and American revolutions). In this foundation myth, war and violence are not even mentioned as constitutive of the rise of the West. Andrews (2021:xiii) highlighted how racism, enslavement, genocides, epistemicides, colonialism, racial capitalism and heteronormative-patriarchal sexism were the foundation of the West. To explain the return of imperialism and imperialist wars, Andrews introduced the concept of ‘colonial nostalgia’ and ‘empire 2.0’ as informing Trumpism (‘Make America Great Again’) and Putinism (Make Russia Great Again) (Andrews 2021:xviii). The Russia–Ukraine War has provoked a number of questions about global, regional and national politics in a world characterised by increased global human entanglements on the one side, and, on the other side, an internationalism constituted by multiplexities and heterarchies of power that defy binary thinking. The question of how to make sense of the global South’s perspectives on the Russia–Ukraine War lies at the centre of rethinking internationalism itself, because it was from the global South that calls for a new egalitarian and racism-free internationalism were made. Adom Getachew, in Worldmaking after Empire: The Rise and Fall of Self-Determination (2019), revealed that African, African-American and Caribbean anticolonial nationalists were concerned not only about nation-building but also responded to the experience of racialised sovereign inequality by directly challenging international racial hierarchies of power while making a strong case for alternative visions of the world. The Russia–Ukraine War has ignited complex questions of hierarchies of power, anti-imperialism, neutrality and non-alignment, arising not only from the way the states of the global South have responded to the apportionment of blame for the war but also how great powers treat smaller states. These questions of caution, non-alignment, neutrality and anti-imperialism are reflected in the voting patterns of states from the global South in the United Nations General Assembly vis-à-vis punishments to be imposed on Russia. The USA and the EU have openly singled out Russia as the aggressor that has to be isolated, sanctioned and punished. However, so far, the USA and the EU have not yet managed to pull the rest of the world onto their side. The phenomenon of abstentions on resolutions aimed at punishing Russia as an aggressor has characterised the voting patterns of a majority of the states from the global South. For example, the voting patterns on the resolution to suspend Russia from the United Nations Council on Human Rights delivered fifty-eight abstentions (mainly from the global South), ninety-three votes in favour (mainly from Europe), and twenty-four against. What does this mean? At one level, does this reflect the incoherence of the current neoliberal internationalism against all efforts of the USA to rally behind it what it considers to be democracies? In his speech delivered on 26 March 2022 at the Royal Castle in Warsaw in Poland, US President Joe Biden defined the Russia–Ukraine War as ‘a battle between democracy and autocracy, between liberty and repression, between a rules-based order and one governed by brute force’. In terms of the resolution of the Russia–Ukraine War, Biden revealed the broader US imperial design of initiating regime change in Moscow. ‘For God’s sake, this man cannot remain in power,’ he urged, in reference to Russia’s President Vladimir Putin. Currently, the US is actively trying to rally behind it what it conceives as democracies, but there are also stark signs and realities of a deeper and complex fragmentation of the existing internationalism. It is not easy to simply draw a line between the allies of the US and its foes aligned with Russia. Complexity and entanglement are the signatures of the current internationalism. The imperial US strategy of regime change has not been successful in other parts of the world — it has left political turmoil and humanitarian disasters in its trail. One can refer to Afghanistan, Iraq and Libya. One can also aver that if implemented in Eurasia, chaos will reign in that region. The other baffling tendency is how the USA and the EU seem to prefer arming Ukraine to seeking peaceful means of resolving war. The voices urging mediation seem to be coming from the global South. South Africa offered to mediate and refused to take sides. The Arab League also offered to mediate. Turkey has hosted one of the meetings. Israel has also indicated its availability to mediate. Below is a broad overview of complex global South perspectives and responses to the Russia–Ukraine War. The Middle East Region Since the end of the Cold War, the Middle East region has been a theatre of wars, in which the great powers have been and are heavily embroiled. The long-standing and ongoing Israel–Palestine conflict reflects clearly the question of Zionist coloniality, which is sanitised by a neoliberal internationalism that is itself not decoupled from coloniality. Russia and the US have been heavily involved in the Syrian crisis. In Iraq, the site of the Gulf War in which regime change was implemented, hell was let loose and more violence and wars ensued after the Anglo-American military invasion and the killing of Sadam Hussein. At the same time the Middle East is not yet free from what Edward Said (1978) named as Orientalism, which has mutated into what is known as Islamophobia. Samuel P. Huntington (1996)’s thesis of ‘the clash of civilisations’ was conceived in relation to Islamic civilisation clashing with the West. Mahmood Mamdani (2004)’s notion of ‘good Muslim, bad Muslim’ emerged within a context in which he was making sense of Islamophobia and what the USA declared the ‘war on terror’, following the 9/11 attacks. The Middle East is a very complex region with equally complex politics of affiliations and difference. What seems to be determining the perspectives from the Middle East are history, memory, interests and considerations of the preservation of sovereignty. History and memory relate the legacies and realities of great power interventions as well as the treatment of refugees from the Middle East in Europe. Neither the Israel–Palestinine conflict nor the war in Syria have attracted as much attention from the world as the Russia–Ukraine War, nor have their refugees received the same welcome compared to the Ukrainian refugees. This raises the question of the hypocrisy of the so-called free world and its racial profiling of people from the Middle East. However, the rich Arab countries themselves have not expressed any enthusiasm to welcome Syrian refugees either, an indication the failure of the strong pan-Arabism that the Arab League has been trying to forge. All these factors have shaped perspectives of the Middle East on the Russia–Ukraine War. While there is a view that the war is a European one, there is also a realisation that it is a European crisis with implications for the Middle East. The Middle East, like other regions of the world, is entangled in particular ways with both Russia and the USA in many domains. Russia is a major exporter of food to the Middle East, particularly wheat. For the Middle East to quickly sign or vote for the sanctioning of Russia will definitely affect food imports from Russia to the region. Thus, just like Europe, which is dependent on oil and natural gas from Russia, the Middle East is cautious not to harm its imports from Russia. While the dominant position of most Arab States at the United Nations General Assembly was to condemn the Russian invasion (thirteen voted in favour, one against, four abstained and one did not vote during the first UN resolution on Russia immediately after its invasion of the Ukraine), there is a cautionary tone that cuts across the region. There are also mixed reactions informed by such observations as why the Israeli occupation of and war on Palestine has not elicited the same international condemnation. Abstention can be interpreted as a preference for neutrality or non-alignment in a region where war has had long-lasting negative effects. Pinar Tank (2022:1) has described the regional perspectives and responses from the Middle East as ‘instrumental, fluid, and fleeting’. The Middle East is a major source of oil and there is a possibility that if Russia is successfully sanctioned, Europe and the USA will turn to it for alternative supplies. For illustrations of complexity in affiliations and alliances in the Middle East region, it is important to reflect on a few countries. Syria, for example, voted in support of Russia because Russia has been the key supporter and protector of the Assad regime since 2015. For Russia, Syria is a strategic partner that enables it to maintain its base in Tartus, giving it access to the Mediterranean. This is even more important now that, under pressure from NATO and the EU (Tank 2022), Turkey has closed the Bosphorus and Dardanelles straits to the passage of Russian warships. Turkey is a member of NATO but it has offered itself as mediator in the Russia–Ukraine War — for example, the 10 March 2022 meeting between Russian Foreign Minister Sergei Lavrov and his Ukrainian counterpart, Dmytro Kuleba, took place in Turkey. Partly this is because, in the Syrian war, Turkey needs Russian support in keeping Syrian Kurds in check (Tank 2022). But at the same time, Turkey is under pressure from the USA to take sides and even send missiles to Ukraine. Israel is another country that reveals the complexities of multiple affiliations. It has taken a very cautious position on the Russia–Ukraine War. There is a Jewish population in both Russia and Ukraine. The President of Ukraine is a Jew. Zelenskyy has already tried to bring Israel to the side of Ukraine by likening the Russian invasion to the Holocaust. But it is hard for Israel to climb the high moral ground and condemn the Russian annexation of Crimea and invasion of Ukraine when it is also advocating for the annexation of the occupied West Bank. At the same time, Israel is a strong partner of the USA in the Middle East. Since its establishment in 1948, Israel has enjoyed the protection of the USA, which has not been forceful in condemning Zionist coloniality and its violent responses to the Palestinian struggle for self-determination. Then there are the Gulf States, comprising Saudi Arabia and the United Arab Emirates (UAE). The strategy of the Gulf States has been to diversify their partners and affiliations, and as a result they have close relations with Russia and have chosen to be neutral vis-à-vis the Russia–Ukraine War. This position puts the US and EU plans to seek oil from suppliers other than Russia in question, as the Gulf States seem not to be persuaded and have stuck with previous OPEC+ agreements that entail lifting oil prices. Saudi Arabia has very strong ties with Russia including agreements on military cooperation. A plus for Moscow is that through its support for Syria’s Bashar Al-Assad, it has gained favour for standing by and protecting its partners — unlike the USA, which always pushes its former allies under the bus if circumstances change. Then there is the Russia–Iran relationship. Russia had been serving as a key intermediary between Washington and Tehran regarding Iran’s nuclear deal. But now that it is the most sanctioned nation after its invasion of Ukraine, this might have consequences for the Joint Comprehensive Plan of Action (JCPA) that it was mediating. A possibility is that Europe and the USA will lift the embargo against Iran’s oil as they seek new supplies of this resource. Under the embargo, Iran has been dependent on Russia for technology. Sanctions against Russia might bring the two countries even closer and make them more dependent on each other. Russia does not fear a nuclear armed Iran as much as the USA does. The African Region Africa was the last part of the world to experience late colonialism. Consequently, its decolonisation became a twentieth-century phenomenon. The two superpowers — the Union of Soviet Socialist Republics (USSR) and the USA — were deeply involved in the decolonisation and postcolonial dynamics in Africa for their various imperial designs. Geographically, the African region is distant from the theatre of the Russia–Ukraine War. Organisationally, it is still seen as divided into North Africa and Sub-Saharan Africa. Black consciousness and Pan-Africanism have not yet succeeded in uniting the continent. Africa remains a divided region in many ways and the African Union (AU) has not been successful in rallying a common African position on the Russia–Ukraine War. At the same time, African leaders have been consistent in their defence of territorial sovereignty to the extent that they maintain inherited colonial boundaries and insist on their inviolability. It was the Congo Crisis of 1960, which resulted in the assassination of Patrice Lumumba, that revealed in stark terms the consequences of great power machinations in postcolonial Africa. Lumumba was a committed nationalist who in his independence speech promised to take the Democratic Republic of Congo (DRC) on an independent national and pan-African trajectory. However, Belgium, the exiting colonial power, was not committed to letting go of the resource-rich DRC. The same was true of the other great powers. Consequently, the DRC became the site of the first neocolonial war involving the great powers in Africa. Lumumba was a friend of Kwame Nkrumah. What happened to Lumumba and the DRC prompted Nkrumah to research and explain neocolonialism and its dangers. The result was the book, Neo-Colonialism: The Last Stage of Imperialism (1965). Barely a year after this publication, Nkrumah suffered a CIA-sponsored military coup in 1966. It was such experiences that combined to reinforce a general anti-imperialist position in Africa and sustain the rhetoric of Pan-Africanism. On 28 February 2022, the African Union issued a statement condemning the reported ill-treatment of Africans trying to leave Ukraine. However, when it came to the United Nations General Assembly resolutions on Russia, African states voted as sovereign individual states rather than as a collective. The continental and regional institutions have been rendered useless by the diverging views among African leaders on the Russia–Ukraine War. A further complication is that African countries such as Egypt, Libya, Tunisia and Algeria have strong links with the Middle East. Just like other regions of the global South, history, memory, realist calculations and other factors determine African perspectives on the Russia–Ukraine War. During the first General Assembly Resolution on Russia, this is how Africa voted: twenty-eight in favour, twenty-six abstained, and one voted with Russia. Debates followed on why Africa voted the way it did so as to arrive at an understanding of the African perspective on the Russia–Ukraine War. The explanations ranged from the historical legacies of solidarity between the Soviet Union and African countries during their anti-colonial/anti-imperialist struggles, to Russia’s current influence on Africa and an Africa that chooses to stick to its tradition of non-alignment. Russia has prominent influence in Burkina Faso, the Central African Republic, Guinea and Mali, where it seems a more preferable partner than France. Through its Wagner Group, Russia has extended its influence to Mozambique, which is battling Islamist insurgents. In the Sahel region, the military leaders who have come to power in recent military coups seem to be inviting Russia to help them tackle jihadists. The twenty-eight African countries that voted in favour of sanctions against Russia included mainly those that have close ties with the United States of America: Botswana, Benin, Cape Verde, Comoros, DRC, Gambia, Ghana, Kenya, Lesotho, Liberia, Malawi, Mauritius, Niger, Nigeria, Sao Tomé and Principe, Seychelles, Sierra Leone, Tunisia and Zambia. Botswana hosts a US military base. The criteria of democracies on the one hand and autocracies on the other hand cannot easily explain the voting pattern, even if some analysts attempted to argue that those African countries that abstained could be categorised as authoritarian or hybrid regimes. Namibia, South Africa and Senegal abstained but they do not qualify as authoritarian regimes by African standards. They have a functioning democracy — albeit with its own problems, like all other democracies across the world. Nigeria and South Africa voted differently — Nigeria in favour, South Africa abstaining. These are two powerful African states. Nigeria had 5,000 students studying in the Ukraine and has strong economic relations with that country. Nigeria therefore voted against Russia but explained its position as being in accordance with the United Nations Charter and in defence of international law. Some analysts pointed out that Nigeria could have taken a position of neutrality because it also imports a lot from Russia and its position could backfire. South Africa, since the time of the Nelson Mandela presidency, has maintained a position that no one can choose its allies and enemies, except itself. This emerged when Mandela was put under pressure by the United States of America to cut ties with Cuba and Libya. Mandela’s response was emphatic — South Africa knew its friends, particularly those that had supported its anti-apartheid struggle wholeheartedly. While circumstances have changed, South Africa has abstained three times since 2 March 2022 from resolutions in the United National General Assembly that were critical of Russia. The Minister of International Relations, Naledi Pandor, and the President of South Africa, Cyril Ramaphosa, explained that their position was not an endorsement of Russia’s invasion of Ukraine. Rather, they preferred to give diplomacy a chance and not take positions that would contribute to the escalation of the war. For example, Minister Pandor argued that the suspension of Russia from the United Nations Council on Human Rights would place it outside international bodies, which would give it an opportunity to escape accountability. There are also very complex histories and realities behind South Africa’s perspective on the Russia–Ukraine War. South Africa, Namibia, Zimbabwe and many other African countries, like Angola and Mozambique, were supported ideologically and materially by the Soviet Union during their wars of liberation. At that time, Ukraine was a republic under the Soviet system and also contributed to the anticolonial and anti-apartheid struggles. This complicates the basis for choosing a position, for South Africa in particular. The second reality is that South Africa is a member of BRICS (Brazil, Russia, India, China and South Africa), which is the forefront of what is termed dewesternisation. But being a regional hegemon, both Russia and the United States of America want South Africa in their corner. Hence, Biden has been putting pressure on South Africa to take a position against Russia. In North Africa, Egypt’s response and perspective on the Russia–Ukraine War is determined by two major factors. The first is economic. Egypt is the world’s top importer of wheat (85%) from Russia and Ukraine. Therefore, any sanctions imposed on Russia and any disruption of wheat production in Ukraine will have direct implications for food security in Egypt. The second factor is the long-standing relations between Egypt and Russia, going as far back as the 1950s (Soviet Union times). Russia supported the construction of the Aswan High Dam in 1964. Currently, Russia is assisting the building of a nuclear plant in El Dabaa in Egypt and Russian companies are active as investors. A Russian Industrial Zone in the Suez Canal Economic Zone is under construction. On top of this, tourism in Egypt is boosted by tourists from both Russia and Ukraine. All these considerations make Egypt very cautious in its response to the Russia–Ukraine War. Egypt is very clear that sanctions imposed on Russia will affect it heavily as is the devaluation of the Russian ruble. Despite its close ties with Russia, Egypt has also strategic partnerships with the USA and the EU. Consequently, a few hours after voting at the UN General Assembly in favour of condemning Russia’s invasion of Ukraine, Egypt issued a statement highlighting the need to pay attention to Russia’s legitimate national security concerns. It also criticised the sanctioning of Russia. Egypt’s actions demonstrate a country that it is walking a tight rope between Russia and the West. As with other regions of the world, Africa needs to consider economic realities, in the form of its imports of wheat, soya bean, barley, sunflower oil and arms from Russia and Ukraine. These factors contribute to Africa taking a neutral and non-aligned position. Africa has multiple external partners across the so-called free world and autocratic world. Countries like Zimbabwe that are under EU and USA sanctions were bound not to support those against Russia. This is another complexity. It would seem for now that non-alignment is the best position for Africa in a world where Cold War fault lines appear to be re-emerging on a global scale. The Asian Region Asia, too, is a highly complex region with several sub-regions, such as Southeast Africa, Central Asia, Western Asia, Asia Pacific and Eurasia. Southeast Asia comprises Brunei, Burma (Myanmar), Cambodia, Indonesia, Laos, Malaysia, the Philippines, Singapore, Thailand, Timor-Leste (East Timor) and Vietnam. These countries, except East Timor, are members of the Association of Southeast Asian Nations (ASEAN). In Southeast Asia, nation-building continues to be a challenge, such as in Indonesia. The construct ‘Asia Pacific’ emerged in the 1960s and 1970s, pushed by countries such as the United States, Japan and Australia, and tended to be used to legitimate United States intervention in East Asian affairs. The Asia-Pacific Economic Cooperation (APEC) of 1989 was one attempt to concretise the construct. It is basically a description of East Asia and the Western powers of the Pacific: United States of America, Australia and Southeast Asia. Then there is Northeast Asia, covering China (including Hong Kong), Taiwan, Japan, South Korea, North Korea, Russia and Mongolia. India is another big piece and power of Asia (McDougall 2016). These geopolitical constructions reflect the complexity of politics and impinge on how Asia as a region exhibits a multiplexity of perspectives vis-à-vis the Russia–Ukraine War. At the centre of Asia is China, which has risen to be a great power and is poised to lead a Sinocentric international world order. One important point about East Asia, according to Kuan-Hsing Chen (2010: 118), is that it is not yet in a post-Cold War era. Korea is still divided. Taiwan is a garrison state. Japan–Russia relations are still characterised by tensions. Sino-American relations have been improving but are not stable. Japan, South Korea and Taiwan are allies of the USA. Sino–Russia relations have improved compared to during the Sino-Soviet disputes. Chen (2010:119) concluded that ‘These are undeniable markers of the continuation and extension of the cold war.’ So far, China has not been vocal against the Russian invasion of the Ukraine. Russia and China belong to BRICS. Shivshankar Menon, a former diplomat who served as National Security Adviser to Indian Prime Minister, Manmohan Singh, from 2010 to 2014, posited five arguments about Asia with regard to the Russia–Ukraine War. The first is that ‘the future global order will be decided not by wars in Europe but by the contest in Asia, on which events in Ukraine have limited bearing’. The second is that ‘Europe is a sideshow to the main theatre of geopolitical drama: Asia’. The third is that ‘the centre of gravity of the world economy has moved from the Atlantic to east of the Urals’. The fourth is that ‘multiple affiliations and partnerships is the norm in Asia, and it will complicate any Western framing of a larger confrontation with the autocracies of China and Russia’. The final point is that Asia’s perspective is determined by a sense ‘of its own difference — its focus on stability, trade, and the bottom line that has served Asian countries so well in the last 40 years’. Menon expressed these opinions in Foreign Affairs, 4 April 2022. Perhaps the example of India helps in demonstrating the complexity if not multiplexity of affiliations and how they are enmeshed in the Russia–Ukraine War. India is a major power in Asia but has close relations with both Russia and the United States of America. But when India began nuclear tests, the USA criticised it and even imposed sanctions. Russia stood by India. It was Russia and France rather than the USA that gave India nuclear reactors. India is also linked with Israel. Israel and the USA supply India with armaments. In the middle of all these complex affiliations, India pursues what has come to be known as ‘strategic autonomy’. This is a realist position in world affairs. To the USA, India is part of the democratic free world and a partner of choice, but at the United Nations General Assembly on 2 March 2022, India abstained from the resolution that demanded that Russia withdraw from Ukraine. India is also not in favour of sanctions being imposed on Russia. Only three Asian countries — Japan, Singapore and South Korea — have joined the USA and EU agenda of sanctioning Russia. There is also a clear message from the Prime Minister of Pakistan, who has taken a clear position that Asians are not slaves of the USA, signalling their non-alignment position. The Latin American Region Latin America is the region closest to the USA. Greg Gandin (2006) depicted it as the ‘empire’s workshop’ to highlight how US imperialism formulated, worked out and tested its imperialist strategies and tactics in Latin America before deploying them around the world. Indeed, the USA has since its emergence as a nation-state-cum-empire claimed Latin America as its sphere of influence. Basically, Latin America ‘has played an indispensable role in the rise of the United States to global power’, in the first instance (Grandin 2006:1). The USA is made of Latin America. In the second instance, Latin America ‘has long served as a workshop of empire, the place where the United States elaborated tactics of extraterritorial administration and acquired its conception as an empire like no other before it’ (Grandin 2006:2). In the third instance: The region provided a school where foreign policy officials and intellectuals could learn to apply what political scientists like to call ‘soft power’ — that is, the spread of America’s authority through non-military means, through commerce, cultural exchanges, and multilateral cooperation’ (Grandin 2006:3). But it was also through the hard power of military interventions and sponsorship of military coups as well as regime changes in Latin America. The USA has never been a good neighbour, and like all other great powers and empires, it has yet to learn good neighbourliness. Consequently, it has committed so many crimes in the Latin American region, ranging from sponsoring regime change to maintaining colonialism, in countries like Puerto Rico. Therefore, the Latin America perspective on the Russia–Ukraine War is informed by long histories and memories going as far back as the Spanish and Portuguese conquistadors. Latin America is also the centre of counter-hegemonic revolutions, from the Haitian Revolution right up to the Bolivarian Revolution. Ideationally, Latin America has offered such schools of thought as Dependency, in the 1970s, and today the coloniality/decoloniality theory, all of which are critical of American and European imperialism and colonialism. The Cuban Missile Crisis of 1962 is being used to compare Russia’s claim that a NATO-and EU-aligned Ukraine is a threat to its security with how the USA responded to the Soviet Union’s attempt to arm Cuba on its border. However, the Latin American perspective — as in other regions — is not homogenous. There is Cuba, an active member and leader of both the Non-Alignment Movement and the Tricontinental Conference, with a long history of resistance to American imperialism and colonialism. Together with countries like Venezuela, Nicaragua and others, it is vehemently opposed to anything to do with the USA and has maintained close ties with Russia. But there are also big countries like Brazil and Mexico, considered to be democracies, which have refused to participate in sanctions against Russia. They have been joined by El Salvador in taking the route of abstention at the United Nations General Assembly on resolutions against Russia. The USA strategy is to mobilise what it calls the ‘free world’ against Russia while at the same time trying to divide even those states that have stood with Russia. In pursuit of this strategy, the USA is trying frantically to cause a split between Russia and China and destroy the Sino-Russia alliance symbolised by BRICS. The President of the United States, Joe Biden, has also revealed a sub-text in that country’s strategy. to engineer regime change in Moscow. The raft of sanctions imposed on Russia might be part of a plan to cause shortages and suffocate the Russian economy so that in the end the people of Russia rise against its government. The second emerging point is that even though there is increasing talk about the return of the Cold War or the emergence of a new Cold War, the realities on the ground are too complex to be reduced to any binary. Affiliations, partnerships and solidarities cut across any fantasy of a democratic and autocratic dichotomy. While the competition is not between Russia and the USA but between USA and China, the revival of Russia and its attempts to move to the East rather than to the West has to be contained in the US’s strategic calculations. The USA calculation was that after the end of the Cold War a pliable Russia would be invited into the EU, NATO and other Euro-North-American-dominated multilateral institutions, such as the World Bank and International Monetary Fund (IMF). The question of national self-determination within internationalism and its future if Russia emerges victorious in the Russia–Ukraine War touches the hearts of smaller states more. Smaller republics and occupied territories like Palestine, Tibet, Kashmir, Taiwan, the Sahrawi Republic and others, which are neighbours to great powers like Israel, China and India for instance, live in fear of invasion and annexation. What is also important is the return of such concepts as non-alignment, neutrality and anti-imperialism and what they mean in the present conjuncture. How adequate, for instance, is the concept of non-alignment in a context where there is only one superpower? Do these concepts of neutrality, non-alignment and anti-imperialism help sufficiently in understanding the current behaviour and response of the global South to the Russia–Ukraine War? So far abstention is linked with non-alignment and neutrality. Does it really indicate neutrality? Abstention is neither yes nor no. How the countries of the global South react to the use of sanctions and their legitimacy in international politics is informed by the fact that this has been a strategy used by great powers against smaller states of the global South. The fact that it has been the smaller and weaker states of the global South that have been victims of sanctions accounts for their ambivalence. Then there is the reality that imposing sanctions on Russia directly affects food security in many countries of the global South. The sanctions even seem to be negatively affecting Europe and the United States, which rely on Russia’s oil and gas. All these issues indicate the complexity of the present conjuncture as well as the crisis of internationalism exposed by the Russia–Ukraine War. There is no doubt that if the Russia–Ukraine War drags on, the perspectives of the global South and responses will become even more complex. What is even more worrying is how Europe and the United States are invested in aggravating the Russia–Ukraine War through supplies of arms and personnel. One wonders whether war can be used to end war?